2007
DOI: 10.1007/s00595-007-3465-0
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Pancreatoduodenectomy (Whipple Procedure) for Massive Upper Gastrointestinal Bleeding Caused by a Diffuse B-Cell Lymphoma of the Duodenum: Report of a Case

Abstract: We herein report a rare case of a massive upper gastrointestinal (GI) bleeding, caused by high-grade diffuse B-cell lymphoma of the duodenum, secondary to immunoproliferative small intestinal disease (IPSID) and treated with an emergency partial pancreatoduodenectomy. A 42-year-old man was admitted to our hospital because of hematemesis. Upper GI endoscopy was unrevealing because of the copious bleeding. Initially, the patient underwent conservative treatment, thus resulting in the temporary cessation of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
1
8
1
Order By: Relevance
“…These publications have shown that salvage resections are associated with increased morbidity and mortality compared to elective procedures. In contrast, very few data are available on primary emergency pancreas resections as these procedures are rarely performed [10][11][12][13][14]. In the present study, we could show that emergency pancreas operations account to a frequency below 1 % in a tertiary referral center with a high overall number of pancreatic operations and full 24/7 emergency service.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…These publications have shown that salvage resections are associated with increased morbidity and mortality compared to elective procedures. In contrast, very few data are available on primary emergency pancreas resections as these procedures are rarely performed [10][11][12][13][14]. In the present study, we could show that emergency pancreas operations account to a frequency below 1 % in a tertiary referral center with a high overall number of pancreatic operations and full 24/7 emergency service.…”
Section: Discussioncontrasting
confidence: 71%
“…Most publications on primary emergency pancreatic operations are dealing with the management of pancreatic injuries following blunt or penetrating abdominal trauma [6][7][8][9]. Beyond these publications on trauma patients, the available literature mainly includes case reports or small patient series [10][11][12][13][14] and show that there is heterogeneity in the indications leading to emergency pancreas operations as well as in the performed surgical procedures [10,11]. However, considerable morbidity and mortality rates have been reported.…”
Section: Abstract Pancreatic Surgery Emergency Morbiditymentioning
confidence: 99%
“…Successful isolated EPD have been also reported for bleeding from duodenal varices [41], diffuse B-Cell Lymphoma of the duodenum [42], giant GIST of the duodenum [43], duodenal paraganglioma [44], and for high flow biliary fistula resulting from a prior right nephrectomy by lumbar approach [45], rupture of a mucinous cystic neoplasm in a pregnant woman [46], ampullary tumor with spontaneous perforation of an aberrant bile duct totally laparoscopically treated [47], and in association with oesophagogastrectomy for caustic injury [48]. Moreover, a large series of 18 patients affected by caustic injuries in which an EPD was associated with oesophagogastrectomy has been reported by Lefrancois, with a mortality rate of 39% (N ¼ 7/18) [49].…”
Section: Discussionmentioning
confidence: 98%
“…Shum et al have presented a case with diffuse large B-cell gastric lymphoma who has arrived to emergency clinic with shortness of breath [8]. In another case by Stratigos et al a 42-year-old man with diffuse large B-cell of the duodenum was admitted to emergency clinic because of massive hematemesis [9]. …”
Section: Discussionmentioning
confidence: 99%